2020
DOI: 10.1007/s11427-019-1624-5
|View full text |Cite
|
Sign up to set email alerts
|

Dissociated deficits in attentional networks in social anxiety and depression

Abstract: A critical cognitive symptom that is commonly involved in social anxiety and depression is attentional deficit. However, the functional relationship between attentional deficit and these two disorders remains poorly understood. Here, we behaviorally disentangled the three key attentional components (alerting, orienting, and executive control) using the established attentional network task (ANT) to investigate how social anxiety and depression are related to deficits in these attention components. We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Regarding our study, the transient tDCS neural boost within the left dlPFC may only benefit those who do require such a neural boost. Prior research indeed reported that individuals with depression or elevated trait anxiety exhibited impairments in the executive conflict network of attention (e.g., DeJong et al, 2019;Hammar et al, 2019;Wang et al, 2020) as well as reduced activation of the dlPFC when performing tasks involving such a network (e.g., Bishop et al, 2009;De Raedt & Koster, 2010;Hu et al, 2017;Wang et al, 2008). Thus, it is not surprising that we should consider the severity of depressive symptoms and trait anxiety for our effects to appear.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Regarding our study, the transient tDCS neural boost within the left dlPFC may only benefit those who do require such a neural boost. Prior research indeed reported that individuals with depression or elevated trait anxiety exhibited impairments in the executive conflict network of attention (e.g., DeJong et al, 2019;Hammar et al, 2019;Wang et al, 2020) as well as reduced activation of the dlPFC when performing tasks involving such a network (e.g., Bishop et al, 2009;De Raedt & Koster, 2010;Hu et al, 2017;Wang et al, 2008). Thus, it is not surprising that we should consider the severity of depressive symptoms and trait anxiety for our effects to appear.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, given that prior studies indicated that social anxiety was associated with tDCS AND ATTENTIONAL NETWORKS 15 impairments in the orienting network of attention but not with the executive conflict network (e.g., Heeren & McNally, 2016;Moriya & Tanno, 2009;Wang et al, 2020), the absence of an association between the former and the improvement of the latter during anodal tDCS should not come as a surprise. In contrast, it echoes research suggesting that interventions aiming at targeting a specific cognitive process should only be delivered in case of exhibited alterations of the incriminated process (e.g., Grafton et al, 2017;Kuckertz et al, 2014;Mogoaşe et al, 2014; but see .…”
Section: Discussionmentioning
confidence: 96%
“…Given the theoretical and metric foundations of the ANT, many scholars have relied on this framework to delineate specific attentional impairments in clinical populations with psychiatric (Gooding et al, 2006;Lannoy et al, 2017;Maurage et al, 2014;Mullane et al, 2011;Urbanek et al, 2009;Wang et al, 2020) and neurological disorders (e.g., Heeren et al, 2014;Maurage et al, 2017;Togo et al, 2015). Moreover, concerning MDD and GAD, the ANT has already been adopted to examine the distinct components of the attentional networks involved in anxiety disorders, with studies pointing to impairment in the orienting network in social anxiety disorder (Heeren and McNally, 2016;Wang et al, 2020) and an impaired executive control network in patients with various other anxiety disorders (Pacheco-Unguetti et al, 2011)-i.e., either GAD, panic disorder, posttraumatic stress disorder, or obsessivecompulsive disorder. Likewise, the ANT has also been implemented in mood disorder research, with several studies relating impaired executive control network in patients with MDD (e.g., Wang et al, 2020) and bipolar disorders (e.g., Gruber et al, 2007;Ossola et al, 2018).…”
Section: Attentional Network In Co-occurring Generalized Anxiety Disorder and Major Depression Disorder: Towards A Staging Hypothesis Of mentioning
confidence: 99%
“…Moreover, concerning MDD and GAD, the ANT has already been adopted to examine the distinct components of the attentional networks involved in anxiety disorders, with studies pointing to impairment in the orienting network in social anxiety disorder (Heeren and McNally, 2016;Wang et al, 2020) and an impaired executive control network in patients with various other anxiety disorders (Pacheco-Unguetti et al, 2011)-i.e., either GAD, panic disorder, posttraumatic stress disorder, or obsessivecompulsive disorder. Likewise, the ANT has also been implemented in mood disorder research, with several studies relating impaired executive control network in patients with MDD (e.g., Wang et al, 2020) and bipolar disorders (e.g., Gruber et al, 2007;Ossola et al, 2018).…”
Section: Attentional Network In Co-occurring Generalized Anxiety Disorder and Major Depression Disorder: Towards A Staging Hypothesis Of mentioning
confidence: 99%
“…Both are common comorbidities of OCD (Pallanti et al, 2011) that may contribute to neuropsychological deficits (Brem et al, 2014; Moritz et al, 2001). For instance, studies that used ANT-R reported that ADHD affects alerting and executive attention (Arora et al, 2020; Berger & Posner, 2000) and that depression affects executive attention (Wang et al, 2020).…”
Section: Introduction1mentioning
confidence: 99%